Kaji Numerik Pengaruh Temperatur Terhadap Ketebalan Lapisan Film Dan Tekanan Pada Roller Bearing Menggunakan Metode Beda Hingga - Lazardo, Iqbal; Cupu, Dedi Rosa Putra; Nazaruddin, Nazaruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The temperature is one of the factors to affect the performance of bearings. High temperatures will decrease the lubricant properties, which its allow direct contact between bearing components. This study examines influencing of the temperature on the pressure of the cylindrical roller bearing and the thickness of film layer in the lubrication of elastohydrodynamic lubrication (EHL) in the contact area. In this research was conducted simulation method by varying the working temperature at 30oC, 60oC, and 100oC. In this simulation applied the finite difference method in solving the Reynolds equation and the pressure-viscosity equation to analyze the EHL pressure and the thickness of the film layer formed. The simulation results were obtained at temperatures of 30oC and 60oC the thickness of the film layer and the pressure forming that were a safe condition. Howaver, the temperature of 100oC was revealed a quite risk (critical) condition due to the thickness of the film layer almost touches zero, which resulted the direct contact (solid contact). Keywords: elastohydrodynamic lubrication, temperature, mineral oil.